Suitability of different levels of sunflower cake from biodiesel production as feed ingredient for lamb production - Monteiro, Lidiane Fagundes da Silva; Melo, Aline Moreira Portella de; Serrano, Martina Pérez; Costa, Roberto Germano; Lima Júnior, Valdi de; Medeiros, Ariosvaldo Nunes de; Lorenzo, José Manuel (Brazilian Journal of Animal Science, 2020)
The objective of this study was to evaluate performance traits, intake, nutrient apparent digestibility, and economic analysis of lambs fed diets containing different levels of sunflower cake (SFC) with a certain chemical composition. Thirty-six Santa Inês × Dorper lambs (n = 9 per treatment diet) with an average body weight (BW) of 19.5±2.19 kg at the beginning of the study were randomly allocated to four isocaloric and isonitrogenous diets for 63 days. A control diet without SFC was compared with diets containing 5, 10, and 15% of dietary dry matter (DM) of SFC replacing soybean meal and corn. Growth performance and economic indicators were calculated. Moreover, individual faeces were collected using canvas bags to evaluate the apparent digestibility of nutrients between days 30 and 45 of study. The total BW gain linearly decreased with the inclusion of SFC in the lamb diet. However, no differences among treatments were observed for final BW, average daily gain, average daily feed intake, or feed conversion ratio. The inclusion of different levels of SFC in the diet reduced the intakes of DM as g/kg BW and non-fibre carbohydrates on DM basis. The apparent digestibility of all nutrients studied improved with the inclusion of 5% SFC but decreased with diets containing 10 or 15% of SFC. Moreover, the higher benefit:cost ratio was obtained for diet containing 5% SFC. Therefore, SFC from biodiesel production could be used at levels of 5% in lamb rations, reducing feeding costs without worsening productive performance, nutrient intake, and digestibility at the ages studied
Keywords: digestibility; byproduct; consumption; economic analysis; performance traits